1991
DOI: 10.1080/08905439109549797
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plantlet regeneration ofTheobroma cacao

Abstract: Somatic embryogenesis was observed on cacao (Theobroma cacao L.) expiants obtained from white to white-pink zygotic embryos of variety 'Amelonado' cultured on media supplemented with napthalene acetic acid (NAA), 1-32 μM, after six weeks of culturing. A high incidence of development-arrested somatic embryogenesis (50%) occurred with expiants cultured in Murashige and Skoog medium containing 32 uM NAA, 0.10% casein hydrolysate and 3.0% sucrose. Embryogenesis rates were different among zygotic embryo expiants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…With the increase of hormone, more and more amount of calli was formed. Wen et al (1991) also reported the same findings that the higher concentration of IAA in the media produced more amount of calli.…”
Section: Callogenesis Response Using Iaa In Ms Mediumsupporting
confidence: 55%
“…With the increase of hormone, more and more amount of calli was formed. Wen et al (1991) also reported the same findings that the higher concentration of IAA in the media produced more amount of calli.…”
Section: Callogenesis Response Using Iaa In Ms Mediumsupporting
confidence: 55%